Assessing the barriers and facilitators of climate action planning in local governments: a two-round survey of expert opinion - Steven Dodd; Scott Butterfield; Jessica Davies; Mette Kragh Furbo; Abigail Morris; Heather Brown (BMC, 2023)
Abstract Background Climate change is one of the greatest threats to public health in this century. The UK is one of six countries that has enshrined in law a commitment to become net zero by 2050. However, there is a lack of guidance and structure for local government in the UK, which has responsibility for public health, to reach this goal and help their communities mitigate and adapt to the health and health inequality impacts of climate change. This study aimed to identify common barriers and facilitators related to addressing the health and health inequality impacts of climate change in local governments. Methods Using Normalisation Process Theory, we developed a two-round survey for people working in local authorities to identify the barriers and facilitators to including the health and health inequality impact of climate change in their climate action plans. The survey was delivered online via Qualtrics software. In the first-round respondents were able to express their views on barriers and facilitators and in the second round they ranked common themes identified from the first round. Two hundred and fifty people working in local government were invited to take part and n = 28 (11.2%) completed the first round of the survey and n = 14 completed the second round. Thematic analysis was used in Round 1 to identify common themes and weighted rankings were used to assess key barriers and facilitators in Round 2. Results Key facilitators were the need to save money on energy, and successful partnership working already in place including across local government, with local communities and external stakeholders. Key barriers were insufficient staff, resources and lack of support from management/leaders, and lack of local evidence. Conclusion To mitigate and adapt to the health impacts of climate change, local government must nurture a culture of innovation and collaboration to ensure that different departments work together This means not just working with external partners, but also collaborating and co-producing with communities to achieve health equity and mitigate the debilitating effect of climate change on public health.